Traitor to Livonia? The Teutonic Orders’ land marshal Jasper van Munster - Mol, Johannes A. (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2015)
One of the main factors contributing to the collapse of the Livonian Confederation in the 1560’s was the disagreement within the Livonian branch of the Teutonic Order over the course of action and response to the Russian threat and the power play of young Ivan IV. The Dutch born Land Marshal Jasper von Munster, the pre-eminent candidate to succeed the aged Livonian Master Heinrich von Galen, was convinced that Livonia could only maintain itself against the new tsar if it entered into a prolonged alliance with Poland, accepting a partial sacrifice of its autonomy. He met with fierce opposition from a group of Order’s dignitaries, led by Wilhelm von Furstenberg, who opposed any rapprochement to Poland. This paper examines why Munster was defeated even though his political line proved to be the soundest. The study adopts a biographical approach and focuses on the Land Marshal’s actions in the opening phase of the Livonian Crisis in the years 1554–1556. It is argued that initially Munster did not plot against the Order’s leadership together with the archbishop of Riga Wilhelm. This happened only in April 1556, long after Furstenberg had convinced Master Galen and the majority of the Order’s officials to support him by acting as coadjutor before he had been formally elected to that position. The prevailing assumption in Baltic historiography that Munster had ‘treacherously’ aimed to secularize the Teutonic state to become its new ruler has to be rejected because Munster at that time was too old to start a dynasty. His actions, though tactically clumsy, seem to have been motivated by genuine concern over the threat of unchristian, in his eyes, Moscow.